Photoelectric effect experiment for understanding the concept of quantization of radiation energy - Yeimy Gerardine Berrios Saavedra; Mayra Alejandra Ramos Bonilla (Góndola, Enseñanza y Aprendizaje de las Ciencias, 2016)
This study forms part of research on the teaching of physics. The question that directed it was: How a proposed classroom, based on the photoelectric effect experiment helps pres-service teachers of physics of the Universidad Pedagógica Nacional to expand their understanding of the concept of quantization energy of radiation? The construction of the theoretical framework developed on the one hand, with scientific ideas about the quantization of energy, and moreover, with the educational proposals of teaching for understanding. This pedagogical approach was guided by the investigative gaze of the study methodology based on design, taking as main element the use of learning tools such as the task to Predict, Experiment and Explain (PEE). It was found that these tasks fomented the initial understandings of students about the concept, while they enriched and transformed progressively their models and scientific ideas, promoting aspects of scientific work in developing curiosity, imagination and motivation.